Skrining Tumbuh Kembang Pada Anak - Yulia Devi Putri; Isna Aglusi Badri; Dedy Siska (Pusat Riset dan Inovasi Nasional, 2023)
Basically, parents are obliged and responsible in the task of educating children by providing various matters concerning the interests of their children, such as developing abilities, knowledge, skills, and maintaining children's health. This is because the activities carried out by children at home are more about emphasizing the ability to speak and tell stories, activities carried out by the question and answer method. While early childhood is easier to understand and understand if learning is applied directly to practice/using media, children will easily remember it because they are directly involved in the learning activity.